2016
DOI: 10.1080/03009734.2016.1194503
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey on family intentions and fertility awareness in women and men in the United Kingdom and Denmark

Abstract: BackgroundAcross several European countries family formation is increasingly postponed. The aims of the study were to investigate the desire for family building and fertility awareness in the UK and Denmark.MethodsA population-based internet survey was used among women (n = 1,000) and men (n = 237) from the UK (40%) and Denmark (60%). Data covered socio-demographics, family formation, and awareness of female age-related fertility. Data analysis used descriptive statistics and logistic regression analysis for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
2
37
2
1
Order By: Relevance
“…Some studies found that men overall had less knowledge about fertility [22, 25, 34], which is in line with the conclusion from Bunting et al, who investigated several knowledge areas including basics facts about infertility and indicators for reduced fertility [23]. In our study the participants generally lacked knowledge on fertility issues, but there were no substantial differences between the two genders.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some studies found that men overall had less knowledge about fertility [22, 25, 34], which is in line with the conclusion from Bunting et al, who investigated several knowledge areas including basics facts about infertility and indicators for reduced fertility [23]. In our study the participants generally lacked knowledge on fertility issues, but there were no substantial differences between the two genders.…”
Section: Discussionsupporting
confidence: 88%
“…Adding to this concern, the majority of participants stated wanting two children, but the current reproduction rate in Denmark is 1.69 [18] showing a potential disparity between what is desired and the actual outcome. The interaction between fertility knowledge and family intentions is not well documented, but a recent European study found that women, who under-estimated the impact of age on fertility, desired to have their first child at a higher age [34]. More studies are needed to confirm these results, but the necessity of fertility education on the ‘optimal’ timing of parenthood seems evident.…”
Section: Discussionmentioning
confidence: 99%
“…Male respondents provided responses that significantly overestimated female fecundity especially at advanced ages, compared to the female respondents. This agrees with results of other studies which showed that males had lower fertility knowledge compared to females [35] [48]. A large proportion of both genders didn't know the accurate female fertile period within a menstrual cycle.…”
Section: Discussion and Theoretical Implications Of Study Findingssupporting
confidence: 92%
“…This finding of this investigation differs from that of previous studies performed with university students. In many studies knowledge levels of female students were reportedly higher [13,15,19] , however Sørensen et al [20] reported lack of any difference in knowledge levels between male, and female students. The difference favouring male students, was thought to be related to increased sexual experience, and higher frequency of sexual intercourse among male students.…”
Section: Discussionmentioning
confidence: 99%